Robert B. Denhardt (2008) Theories of Public Organization 5th California: Thomson Wadsworth. Pp. 222. ISBN 978-0-495-09706-8 - vorathumdusdee, dusadee (King Prajadhipok’s Institute Journal, 2020)
Robert B. Denhardt (2008) Theories of Public Organization 5th California: Thomson Wadsworth. Pp. 222. ISBN 978-0-495-09706-8